Systematic Assessment Model for Sustainability Reporting in the Malaysia Context - Wan Nurul Syahirah, Wan Lanang; Faiz, Mohd Turan; Kartina, Johan (Universiti Malaysia Pahang, 2017)
Sustainability assessment is gaining interests and increasingly recognized as a powerful and important tool to measure the performance of sustainability in a company or industry. Nowadays, there are many existing tools that the users can use for sustainable development. There are various initiatives exists on tools for sustainable development, though most of the tools focused on environmental, economy and social aspects. Using the Green Project Management (GPM) P5 concept that suggests the firms not only needs to engage in mainly 3Ps principle: planet, profit, people responsible behaviors, but also, product and process need to be included in the practices. This study will introduce a new mathematical model for assessing the level of sustainability practice in the company. Based on multiple case studies, involving in-depth interviews with senior directors, feedback from experts, and previous engineering report, a framework is proposed with the aims to obtain the respective data from the feedbacks and to develop a new mathematical model for reducing the variation. Lastly, to develop a matrix for a systematic sustainability assessment model for sustainability reporting. This study is expected to provide a guideline to the company to assimilate the sustainability assessment in their respective development stage.